2018
DOI: 10.1021/acs.est.7b06270
|View full text |Cite
|
Sign up to set email alerts
|

Bisphenol F Disrupts Thyroid Hormone Signaling and Postembryonic Development in Xenopus laevis

Abstract: The safety of bisphenol A (BPA) alternatives has attracted much attention due to their wide use. In this study, we investigated the effects of bisphenol F (BPF), an alternative to BPA, on thyroid hormone (TH) signaling and postembryonic development in vertebrates using T3-induced and spontaneous Xenopus metamorphosis as models. We found that in the T3-induced metamorphosis assay, higher concentrations of BPF (100-10000 nM) antagonized T3-induced TH-response gene transcription and morphological changes includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…When screened for activity in a yeast activity assay BPF was shown to have antagonist effects on the androgen receptor as well as glucocorticoid receptor, and in both cases the potency of BPF was slightly higher than BPA (Roelofs et al 2015). Recent studies have shown that, similar to BPA, BPF has the potential to interfere with the thyroid hormone (TH) signaling pathway (Zhang et al 2018;Zhu et al 2018). A final point is that multiple bisphenols are being detected in human tissues and the manner in which these compounds interact is nearly completely unknown (Kolatorova et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…When screened for activity in a yeast activity assay BPF was shown to have antagonist effects on the androgen receptor as well as glucocorticoid receptor, and in both cases the potency of BPF was slightly higher than BPA (Roelofs et al 2015). Recent studies have shown that, similar to BPA, BPF has the potential to interfere with the thyroid hormone (TH) signaling pathway (Zhang et al 2018;Zhu et al 2018). A final point is that multiple bisphenols are being detected in human tissues and the manner in which these compounds interact is nearly completely unknown (Kolatorova et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Following this, the first-strand cDNA was stored at −20 °C for gene expression analysis. Expression of TH-response genes was analyzed using SYBR Green I with the Real-time Polymerase Chain Reaction system (Light Cycler 480, Roche, Basel, Switzerland), with Ribosomal protein L8 ( rpl8 ) as a reference gene [ 43 , 44 , 45 ] and the expression of rpl8 was not affected by treatments ( Supplementary Materials, Figures S1 and S2 ). In 10 µL of PCR reaction system, 1 µL of cDNA template, 0.3 µL of forward primer, 0.3 µL of reverse primer, 3.4 µL of DNase/RNase-free water, and 5 µL of 2 × SuperReal PreMix Plus were mixed.…”
Section: Methodsmentioning
confidence: 99%
“…While the majority mainly differ in exposure period and sometimes in the model employed, many of the same endpoints were investigated to identify potential THADCs (i.e., hindlimb length, snout-to-vent length, developmental stage and thyroid histology; Supplementary Table). In tadpoles, as morphological changes of the head region and the brain are induced by THs, measurements such as mouth width, head area, brain width, brain length, or olfactory-organ-to-brain length may further characterize disruption of TH-induced metamorphosis (Yao et al, 2017;Zhu et al, 2018;Mengeling et al, 2016Mengeling et al, , 2017. Several morphological endpoints were examined in conjunction with the readout of transgenic X. laevis tadpoles harbouring a luciferase reporter driven by TH/BZIP TREs (Mengeling et al, 2016(Mengeling et al, , 2017.…”
Section: Additional Amphibian Assaysmentioning
confidence: 99%